Whole lung lavage: our experience in pulmonary alveolar proteinosis and in type B Niemann Pick disease - Casanova, Serena; Puglisi, Silvia; Gurioli, Carlo; Gurioli, Christian; Maitan, Stefano; Martinello, Sabrina; Sultani, Fabio; Ravaglia, Claudia; Poletti, Venerino (Rassegna di Patologia dell'Apparato Respiratorio, 2021)
Whole lung lavage (WLL) is an invasive and safe procedure used for pulmonary alveolar proteinosis (PAP). Despite the scientific progress achieved in terms of therapy, WLL remains the gold standard in PAP and could be also applied in other diseases. Here we present a retrospective data collection of 5 patients who underwent to WLL, four suffered from PAP and one suffered from type B Niemann-Pick disease.